Assessing Ontario's Personal Support Worker Registry - Audrey Laporte; David Rudoler (McMaster University Library Press, 2013)
In response to the growing role of personal support workers (PSWs) in the delivery of health care services to Ontarians, the Ontario government has moved forward with the creation of a PSW registry. This registry will be mandatory for all PSWs employed by publicly funded health care employers, and has the stated objectives of better highlighting the work that PSWs do in Ontario, providing a platform for PSWs and employers to more easily access the labour market, and to provide government with information for human resources planning. In this paper we consider the factors that brought the creation of a PSW registry onto the Ontario government's policy agenda, discuss how the registry is being implemented, and provide an analysis of the strengths and weaknesses of this policy change. Prenant acte du rôle de plus en plus important joué par les préposés aux services de soutien à la personne (PSSP) dans les soins fournis aux Ontariens, le gouvernement de l'Ontario a décidé de créer un registre des PSSP. L'inscription dans ce registre sera obligatoire pour tout PSSP travaillant pour des employeurs financés sur fonds publics et les objectifs suivants sont poursuivis : mettre en valeur le travail des PSSP en Ontario, fournir un point d'accès au marché du travail pour les PSSP et leurs employeurs, et fournir au gouvernement l'information nécessaire pour planifier les ressources humaines dans ce domaine. Dans cet article, nous décrivons les facteurs expliquant comment la décision politique de créer un registre des PSSP a été prise, nous discutons la façon dont celui-ci est mis en place, et nous proposons une analyse des forces et limites de cette décision politique.